EFFECTS OF CONCENTRATE LEVELS AND OIL SUPPLEMENTATION IN DIETS ON RUMEN CHARACTERISTICS AND PERFORMANCE OF CATTLE - N. T. Ngu; N. T. H. Nhan; N. V. Hon; L. T. Danh; Duong Minh Vien; Luu Huynh Anh; Nguyen Hong Xuan (Journal of Animal and Plant Sciences, 2019)
This study investigated the effects of concentrate levels and oil supplementation on rumen characteristics and growth performance of cattle. Twenty-four Brahman crossbred bulls were arranged in a 2x3 factorial design with two levels of concentrate (0.5 and 1.5% body weight) and three supplemental sources (60 g soybean oil/kg dry matter (DM), 60 g fish oil/kg DM and non-oil). Total rumen bacteria number was higher in cattle fed diets with lower concentrate level (P≤0.05), yet it was not affected by oil supplementation. Acetic and butyric acid concentration in rumen decreased with the increase of concentrate level in diet. The intake of total DM and crude protein were higher in cattle fed higher concentrate diet (6.25 kg/day and 778 g/day, respectively). In terms of growth performance, the higher concentrate level cattle consumed, the better weight gain was achieved (768 g/day). Soybean oil addition helped attain the highest weight gain of 738 g/day, while similar weight increase was observed in cattle fed non-oil and fish oil supplemented diets (624 g/day and 641 g/day, respectively). Supplementation of concentrate and oil also increased weight gain and the maximum daily weight gain (851 g/day) was recorded in cattle fed the diet containing soybean oil combined with 1.5% concentrate.
Keywords: cattle; concentrate; fish oil; soybean oil; weight gain; rumen fermentation